2016
DOI: 10.1186/s40064-016-2245-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of patient controlled analgesia (PCA) using dexmedetomidine and propofol during septoplasty operations: a randomized clinical trial

Abstract: IntroductionSeptoplastical surgery to correct septum deviation can be performed under either local or general anesthesia. During local anesthesia, sedation helps to provide minimum anxiety/discomfort. Our aim was to evaluate the effects of patient-controlled analgesia using dexmedetomidine and propofol on sedation level, analgesic requirement, and patient satisfaction.Study designA prospective, randomized-parallel clinical study.MethodsFifty patients undergoing septoplastical surgery at our university hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Similar to our study, previous studies demonstrated that dexmedetomidine was associated with lower post-operative VAS score compared to the propofol. 8,10,16 We also showed that the post-operative Riker SAS score was significantly lower in the dexmedetomidine group compared to the propofol group. Based on these results, we can conclude that dexmedetomidine provides more advantages than propofol as a sedative agent during hysteroscopic surgery.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations
“…Similar to our study, previous studies demonstrated that dexmedetomidine was associated with lower post-operative VAS score compared to the propofol. 8,10,16 We also showed that the post-operative Riker SAS score was significantly lower in the dexmedetomidine group compared to the propofol group. Based on these results, we can conclude that dexmedetomidine provides more advantages than propofol as a sedative agent during hysteroscopic surgery.…”
Section: Discussionmentioning
confidence: 56%
“…Wang et al showed that post‐operative pain score was significantly lower in the dexmedetomidine group compared to in the propofol group in patients undergoing inguinal hernia repair procedure. Akça et al found that dexmedetomidine provided more stable and satisfactory sedation than propofol in patients undergoing septoplastical surgery. Finally, Xu et al demonstrated that dexmedetomidine provided safer and more effective sedation than propofol in patients undergoing uvulopalatopharyngoplasty procedure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Outcomes analyzed were intra‐ and postoperative pain; postoperative (24 hours) analgesic requirements (dose of postoperative opioids or nonopioid analgesics); occurrence of postoperative nausea and vomiting (PONV) (incidence or percentage of patients); intraoperative hypotension; intraoperative bradycardia; intraoperative desaturation; occurrence of patient satisfaction (incidence or percentage of patients); and operative blood loss . In the enrolled study for analgesics, one study used diclofenac (nonsteroidal antiinflammatory drug) as the additional analgesic, and the remaining studies used opioids such as tramadol and fentanyl as the additional analgesics. In terms of bradycardia and hypotension, these states were defined as the hemodynamic instabilities to be treated with 0.5 mg of atropine injection or 5 mg of ephedrine injection individually, and were monitored at regular intervals during the operation.…”
Section: Methodsmentioning
confidence: 99%